Protective effects of Majun Brahmi on aluminium-induced cognitive impairment in rats: Biochemical and behavioral changes - Monika Kumari; Jha, Puja Kumari; Khan, Mahmood Ahmed; Amjad Saifi; Arora, Vinod Kumar; Sumita Halder; Yasmeen Shamsi; Rafat Sultana Ahmed (Asian Journal of Medical Sciences, 2023)
Background: The Unani formulation Majun Brahmi (MB), a combination of herbs, is used in India as a brain tonic and memory enhancer. Aluminium deposition in the brain is associated with the development of neurodegenerative diseases. Aims and Objectives: The present study was designed to observe that the effects of MB have been evaluated on aluminium trichloride or aluminium chloride (AlCl3)-induced cognitive impairment in an experimental rat model. Materials and Methods: Twenty male Wistar albino rats were divided into four groups of five rats each. AlCl3 was administered orally for 30 days to induce cognitive impairment. Group I received saline, Group II-AlCl3 (100 mg/kg b.wt), Group III-MB (1027.77 mg/kg b.wt), and Group IV-AlCl3 + MB (100 mg/kg b.wt+1027.77 mg/kg b.wt). At the end of the experiment, rats were subjected to behavioral and biochemical assessments. Results: Animals treated with AlCl3 showed a significant increase in time to reach the platform in the Morris water maze test (MWM), prolonged transfer latency (TL) in the elevated plus maze, and decreased step-down latency in the passive avoidance test, as compared to controls (P<0.01). Cotreatment with MB resulted in a reduced time to reach the platform in MWM, increased step-down latencies, and decreased TL. AlCl3 induction significantly increased malondialdehyde and decreased superoxide dismutase, glutathione reductase, glutathione, total antioxidant capacity, and catalase levels. Concomitant administration of MB significantly attenuated the effects AlCl3 on lipid peroxidation and restored the reduced antioxidant parameters. Conclusion: The study provides strong evidence for the potential use of MB in the treatment of neurodegenerative disorders like Alzheimer’s disease.